2022
DOI: 10.1002/ags3.12566
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and long‐term postoperative outcomes in patients with postoperative dysphagia after esophagectomy for esophageal cancer

Abstract: Aim: Dysphagia is one of the most common complications after esophagectomy.However, no study has investigated the long-term postoperative outcomes in patients with postoperative dysphagia. Here, we aimed to identify risk factors for postoperative dysphagia and to investigate long-term postoperative outcomes in such patients.Methods: This study included 304 consecutive patients with thoracic esophageal cancer who underwent curative esophagectomy. They were diagnosed with postoperative dysphagia through a contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“… 21 In addition, patients with esophageal cancer often develop various postoperative complications, such as dysphagia, pneumonia, micronutrient malnutrition, and weight loss. 16 , 22 , 23 They may have an increased risk of developing osteoporosis after esophagectomy. However, BMD changes in postoperative patients with esophageal cancer have not been evaluated well.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 21 In addition, patients with esophageal cancer often develop various postoperative complications, such as dysphagia, pneumonia, micronutrient malnutrition, and weight loss. 16 , 22 , 23 They may have an increased risk of developing osteoporosis after esophagectomy. However, BMD changes in postoperative patients with esophageal cancer have not been evaluated well.…”
Section: Discussionmentioning
confidence: 99%
“…Pickhardt et al demonstrated that trabecular attenuation values for the vertebral bodies on CT scans could be used to estimate BMD. 16 , 17 Because normative ranges for L1 trabecular attenuation have been established for all ages, direct HU measurements from diagnostic CT scans can be helpful and reliable for opportunistic use in osteoporosis screening. 24 Third, although we revealed the incidence of osteoporosis after esophagectomy, we could not investigate bone fracture and the long‐term quality of life in patients with osteoporosis after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations